APPLICATION OF STEM CELLS AND THEIR DERIVATIVES AS DRUG DELIVERY SYSTEMS - Ambarura, Elsa; Sudirman, Clarissa (Journal of Stem Cell Research and Tissue Engineering, 2025)
Advances in modern drug delivery systems (DDS) are increasingly shaped by the need to improve therapeutic precision while minimizing systemic toxicity. Stem cells and their derivatives—particularly mesenchymal stem cells (MSCs)—have emerged as highly promising platforms due to their intrinsic homing capacity, immunomodulatory properties, and compatibility with molecular engineering. This review synthesizes recent progress in whole-cell, secretome-based, and extracellular vesicle (EV)/exosome-based DDS, highlighting their biological mechanisms, engineering innovations, and translational challenges. Whole-cell delivery systems exploit the ability of living stem cells to migrate toward tumors or inflamed tissues while carrying therapeutic agents such as paclitaxel or oncolytic viruses, enabling site-specific drug release with enhanced local potency. Complementarily, MSC secretome—rich in soluble factors and vesicles—demonstrates synergistic cytotoxic, anti-inflammatory, and microenvironment-modulating effects that strengthen therapeutic outcomes. Exosomes and EVs offer nanoscale, low-immunogenic carriers capable of transporting small-molecule drugs, siRNA, or immunotherapeutic combinations, with engineering strategies such as surface functionalization, electroporation, and genetic modification further improving cargo loading, targeting specificity, and stability. This review employed a structured literature search (2020–2025) across PubMed and Google Scholar, followed by rigorous screening and qualitative synthesis of eligible preclinical and clinical evidence. Key translational barriers include large-scale manufacturing, batch variability, pharmacokinetic limitations, and regulatory ambiguity surrounding stem-cell-derived therapeutics. Emerging GMP-compatible pipelines and gene-edited stem cell systems show promise in addressing these hurdles. Overall, stem cell–based DDS represent a rapidly evolving biological technology ecosystem, integrating natural cellular behaviors with engineered precision. Their versatile platforms hold substantial potential for targeted cancer therapy, immune modulation, and RNA interference–based treatments, positioning them at the forefront of next-generation therapeutic delivery strategies.